(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2023)
This photographic essay is offered as a reflective gallery space among the text-based debate, ideas, arguments, and opinions in this special edition. On 14 August 1985, I had a falling out with my friend and fellow musician and musicologist David Johnson (1942-2009), on account of a review I had written of his seminal book Scottish Fiddle Music in the Eighteenth Century for the journal Cencrastus. I remember the precise date, as David chose to challenge me on the matter while we sat together waiting nervously in the green room at the Queens Hall, minutes before we were to take the stage in Mr Menuhin’s Delight, an Edinburgh International Festival concert of Scottish fiddle music.